Suomen geologinen kartta 1:100000 : kallioperäkarttojen selitykset = Geological map of Finland 1:100000 : explanation to the maps of Pre-Quaternary rocks. Lehdet 2331 ja 2332 = Sheets 2331 and 2332, Kyyjärvi-Perho kartta-alueen kallioperä - Pipping, Fredrik; Vaarma, Markus (Geologian tutkimuskeskus, 2003)
Summary: Pre-Quaternary rocks of the Kyyjärvi and Perho map-sheet areas.
Keywords: geologiset kartat; kallioperä; kartat; geologiska kartor; berggrund; kartor; Kyyjärvi; Perho